Objectivity, epistemic humility and responsible science - Lumbreras Sancho, Sara (Razón y fe, 2020)
Science and technology do not perform their functions in a purely objectively manner, but are rather constructed from the points of view of the individuals who build them, inheriting their virtues and defects. This article describes the individual and group cognitive biases that most negatively affect technoscientific practice and explains undesirable phenomena such as 180 degree turns in medical recommendations. Finally, it proposes some brief lines of action that could be useful in the search for objectivity, centered on humility and responsibility.
Keywords: objectivity; virtue epistemology; cognitive biases; situated knowledge; engineering; medicine